Medición de la discapacidad vocal en los pacientes con nódulos vocales - Halawa, Wasim Elhendi; Vázquez Muñoz, Irene; Santos Pérez, Sofía (Revista de Investigación en Logopedia, 2012)
In order to analyze the degree of handicap that vocal nodules suppose for patients, we present the results of the subjective evaluation (the vocal handicap index (VHI-30) adapted to Spanish language and the evaluation of symptoms associated with dysphonia) in 97 patients diagnosed of vocal nodules. We found a significant degree of handicap showed by high values of VHI-30 (61.18), its three subscales (organic (26.48), functional (21.75) and emotional (12.94)) and a significant degree of impairment caused by the associated symptoms. We compare our results with control groups of our environment and the results were stratified according to the profession of patients. We conclude that the presence of vocal nodules causes a significant grade of disability for social and professional activities and a considerable emotional impact for the patient.
Keywords: Measurement; Vocal handicap; Vocal nodules.